MENINGKATKAN KETERAMPILAN PROSES SAINS PADA ANAK USIA 4-5 TAHUN MELALUI METODE EKSPERIMEN - Nurhayati, Siti; Aisyah, Dewi Siti; Putri, Feronica Eka (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aim of this research is to describe improving science process skills in children using experimental methods. PAUD Naratas Rawamerta Karawang was the location for this research. The 11 Naratas PAUD group A children were used as research subjects. This study uses classroom action research with the Kemmis and McTaggart model, which includes action, planning, reflection, and observation. Observation, interviews, and documentation are the data collection methods used in this research. The results of the research show that experimental techniques can improve the science process skills of group A children at PAUD Naratas Rawamerta. This is proven by the data obtained during pre-action, the percentage reached 30.16%, then increased by 25.11% in cycle I to 55.27% and increased again by 27.73% in cycle II to 83%. These data show that experimental techniques can improve science process skills.